Comparative Anatomical Study of Fimbrial End of Fallopian Tubes in Ectopic Pregnancy - Mahmood, Anjum; Shafiq, Mehak; Qadeer, Robina; Aman, Afrah; Mumtaz, Junaid; Shehzad, Khalid (Journal of Neonatal Surgery, 2025)
Background: Ectopic pregnancy is also a leading death-cause of maternal morbidity with the most prevalent manifestation being tubal implantation. Although the destruction of the fallopian tube has been a focus, scant consideration has been given to the anatomy and microscopic alterations at the fimbrial end which is vital in the ovum capture and transport. Methodology: The study was carried out as a comparative anatomy study in Pak International Medical College, Peshawar, in the period of one year, i.e. January 2024 to January 2025. Seventy-two fallopian tubes were studied that comprised of tubes of surgically treated ectopic pregnancies and a control group of non-pathological gynecology surgeries. The gross anatomical evaluation of fimbrial end was done and histopathological examination was also done using hematoxylin and eosin. The demographic and clinical information was taken and results were tallied using statistical analysis to compare the two groups. Results: Cases of ectopic pregnancy showed extensive structural changes at the fimbrial end characterized by shortening of the fimbrial length, fewer fimbrial projections, and commonly congestion, edema, and adhesions. Microscopic observation showed that epithelial disruption, cilia loss, stromal edema and inflammatory cell infiltration occurred in a high percentage of ectopic samples and was not common in control samples. The difference that was observed was statistically significant. Conclusion: The results of this research show that ectopic pregnancy is associated with the significant anatomical and histological destruction of fimbrial end of the fallopian tube. The possible problems with such changes are that they can disrupt normal ovum transport and cause abnormal tubal implantation. It is possible therefore that preservation of tubal health especially at the fimbrial end is significant in the mitigation of the risk of ectopic pregnancy